System dynamics approach for understanding scheme of Community-Based Adaptation to flooding: The case of a flood-prone district in Vietnamese urban city. Issue 2 (15th March 2022) - Quang Dao, Tran; Thi Thu Huong, Le
ABSTRACT: Community-Based Adaptation (CBA) scheme gives us an insight into how people confront different issues at the community scale. In the context of flooding, it is recognized that there is a remarkable need for analyzing the dynamic characteristics of the CBA scheme, from which we can observe how flood-related factors interact and influence one another. This paper applies the System Dynamics (SD) approach to give a visual demonstration by modeling a Causal Loop Diagram (CLD) of the factors. District 8 in Ho Chi Minh City, Vietnam, is a case study for the implementation of SD for a better understanding of the links and dependencies between the factors collected from historical experience, a questionnaire survey, and an in-depth interview. The interacting parts identified include characteristics of the location, hard measures of local dwellers, and actions of local authorities. The SD model addresses conflicts among adaptation measures explained by reinforcing loops and expressing an unsustainable way of tackling urban floods in the existing scheme at the study location.